1952
DOI: 10.1111/j.1939-0025.1952.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Social structure and interaction processes on a psychiatric ward.

Abstract: HE individual who enters a mental hospital finds himself placed in a T number of new social situations, all of which influence his behavior and treatment. The patient's relationship to his therapist, both in its administrative and therapeutic aspects, has received the most study. This holds true where the course of treatment is through insight psychotherapy (13, 14), and also where it involves a structuring of the patient's social milieu by prescribing how hospital personnel shall react to him (1, 31, 40). Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

1956
1956
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(42 citation statements)
references
References 20 publications
0
39
0
3
Order By: Relevance
“…Jones observed that the social interaction of patients has "therapeutic possibilities" even when staff are not present. In the 1960s, the therapeutic community was proposed as a means of humanizing and improving the effectiveness of psychiatric institutions, even as critics argued that "total institutions" produced the very effects of serious mental illness and chronicity that they purported to treat ( Caudill, Redlich, Gilmore, & Brody, 1952;Goffman, 1961;Szasz, 1961). Gutheil (1985) has suggested that there is a strong family resemblance between the concepts of therapeutic community and MT.…”
Section: Introductionmentioning
confidence: 99%
“…Jones observed that the social interaction of patients has "therapeutic possibilities" even when staff are not present. In the 1960s, the therapeutic community was proposed as a means of humanizing and improving the effectiveness of psychiatric institutions, even as critics argued that "total institutions" produced the very effects of serious mental illness and chronicity that they purported to treat ( Caudill, Redlich, Gilmore, & Brody, 1952;Goffman, 1961;Szasz, 1961). Gutheil (1985) has suggested that there is a strong family resemblance between the concepts of therapeutic community and MT.…”
Section: Introductionmentioning
confidence: 99%
“…Within the colloquia discussion, the lines of collaborative research during the next half century were clearly foreshadowed: the epidemiology of social factors like class and culture as they influenced mental illness, the social organization of hospitals, the basic concepts of therapeutic communities, the interactive effects of mental disorder and families, and a variety of other subjects. A direct product of these meetings were the studies of a mental hospital by Howard Rowland (1938Rowland ( , 1939, establishing a model for combining the theories of Sullivan with the methods of field research developed by Sapir and Park, and their application for the study of mental hospitals over the period of the next 30 years (Belknap, 1956;Caudill et al, 1954;Greenblatt et al, 1955;Goffman, 1961;Stanton and Schwartz, 1954). It can be argued that these were the underpinnings of the therapeutic community movement, later associated with the British psychiatrist Maxwell Jones, and also the community mental health movement in the United States.…”
Section: Colloquia On Personality Investigationmentioning
confidence: 99%
“…The dangers she experienced, however, were not those that might be expected, focusing rather on the harm that researchers could experience in settings where care was sub-standard and abusive Covert research in studying mental illness and the psychiatric system has involved researchers using deception, but has been justified by the understandings and social benefits accrued from it (see Caudill, 1952;Rosenhan, 1973). Rosenhan's study used a deliberate feigning of symptoms by eight people to gain entry different mental hospitals.…”
Section: Covert Researchmentioning
confidence: 99%